Chevaux de travail du XIXe siècle : à la recherche des éleveurs de l’Orne - Agnès Manneheut (In Situ)
Workhorses in the nineteenth century, looking at horsebreeders in the Orne department. For horse breeding, the nineteenth century was a time of specialization, accompanied by the emergence of recognized breeders, and by supervision by various organizations. Through a case study of the department of Orne, reputed for its quality horse-breeding, the purpose of this article is to identify archive and other sources generated about work horses, and to examine how they complement each other and show the reality of breeding and its actors, within the farming and trading contexts.